Transformation of Islamic Law into a Political Historical Law Foundation - Nasir, Ahmad; Nasution, Muhammad Syukri Albani; Siregar, Ramadhan Syahmedi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research aims to analyze the transformation of Islamic law into the foundation of law formation in Indonesia from a historical and political perspective. By using the approaches of Neo-Receptie In Complexu Theory, Maqasid Shari'ah, Max Weber's Socio Legal, and Constructivist Ijtimai Theory, this research identifies the dynamics of political configuration between governments and their influence on the formalization of Islamic law in Indonesia. The main focus is on how Islamic sharia changes from symbolic to substantive in the national legal framework. The method used is qualitative analysis with a historical and political approach, integrating legal and social theories. Literature and document studies were also involved for an in-depth understanding of the topic. The results show that the formalization of Islamic sharia in Indonesia is strongly influenced by the changing political configuration throughout history, starting from the era of Islamic kingdoms, colonialism, to reform. The shift from symbolic to substantive Islam allowed for wider participation of Muslims in socio-political life, reflecting a shift towards inclusiveness without threatening diversity and national unity. The transformation of Islamic law into positive law in Indonesia is the result of a dynamic process influenced by historical and political contexts. Constructivist Ijtimai Theory, with its focus on inclusive dialog and community participation, provides a framework for understanding and promoting this transformation. The research suggests that to achieve substantive Islamic political goals, Islamic political activists should adopt an inclusive approach, utilizing all channels including the bureaucracy in voicing their political aspirations.